Metamaterial extended CSRR based monopole antenna for wideband applications - Bora, Pronami; Mudaliar, Mona; Baburao Dhanade, Yuvraj; Sreelakshm, K; Paul, Chayan; T P Madhav, B (International Journal of Engineering and Technology, 2017)
A metamaterial extended microstrip rectangular patch antenna with CSRR loading and defected ground structures(DGS) is proposed for wideband applications with band notching at the frequencies of KU band. The proposed antenna is designed by embedding it on Rogers RT/Duroid 5880 substrate with good impedance matching of 50 Ω at the feedline. The high frequency structure simulator (HFSS) is used to design and simulate the antennas parameters in the operating band. Measurement results confirm the antenna characteristics as predicted in the simulation with a slight shift in frequencies.